Equity, Growth, and Community What the Nation Can Learn from America's Metro Areas - Pastor, Manuel (University of California Press, 2015)
In the last several years, much has been written about growing economic challenges, increasing income inequality, and political polarization in the United States. Addressing these new realities in America's metropolitan regions, this book argues that a few lessons are emerging: first, inequity is bad for economic growth; second, bringing together the concerns of equity and growth requires concerted local action; and third, the fundamental building block for doing this is the creation of diverse and dynamic epistemic (or knowledge) communities, which help to overcome political polarization and to address the challenges of economic restructuring and social divides. "As America bolts toward a more multiracial future in the face of skyrocketing inequality, local leaders are desperately seeking strategies to foster more inclusive growth. Chris Benner and Manuel Pastor's research uncovers a critical ingredient of success: diverse regional leaders coming together to build a foundation of shared knowledge and advance positive change." - ANGELA GLOVER BLACKWELL, Founder and CEO, PolicyLink CHRIS BENNER is the Dorothy E. Everett Chair in Global Information and Social Entrepreneurship, Director of the Everett Program for Digital Tools for Social Innovation, and Professor of Environmental Studies and Sociology at the University of California, Santa Cruz. His most recent book, coauthored with Manuel Pastor, is Just Growth: Inclusion and Prosperity in America's Metropolitan Region. His other books include This Could Be the Start of Something Big: How Social Movements for Regional Equity Are Transforming Metropolitan America and Work in the New Economy: Flexible Labor Markets in the New Economy. MANUEL PASTOR is Professor of Sociology and American Studies and Ethnicity at the University of Southern California, where he also serves as Director of USC's Program for Environmental and Regional Equity (PERE) and Codirector of USC's Center for the Study of Immigrant Integration (CSII). He is the coauthor of Uncommon Common Ground: Race and America's Future and This Could Be the Start of Something Big: How Social Movements for Regional Equity Are Transforming Metropolitan America.